(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Background & Methodology: This descriptive cross sectional study was conducted to assess the antenatal care practices in some selected rural areas of Bangladesh for a period of six months starting from July to December 2014. The study populations were all married women of reproductive age, who had at least one child and had delivered the last child within two years from the period of data collection. A total of 353 women were selected by convenient type of non probability sampling. A semi-structured pre-tested questionnaire was used which include socio-demographic profile and practice regarding antenatal care. Results: Out of 353 respondents, more than fifty percent of the respondents 271(76.8%) received ante-natal services and of them 157(57.9%) received more than three ante natal care. Only 82(23.2%) respondents did not receive ante natal services. The major reasons for not attending ante natal check up were due to healthy and thought of as not necessary 60 (73.2%), pregnancy is an ordinary issue 20 (24.4%), inability to afford cost 14(17.1%) and feel embarrassed and far distance 24 (24.2%). A significant association was found between education of the respondents and ante-natal service received (P=0.00) and between occupation of the husband and ante-natal service received by the respondents (P = 0.01) and between knowledge on ante-natal services (p=0.00). Conclusion: The monthly family income, age of the respondents and number of living children did not show any significant association on bi-variate analysis. So, the findings of the study suggested that education of the mothers is an important determinant of ante-natal visits during pregnancy. Therefore, information, education and communication on ante-natal services must be intensified in order to reach the rural mothers. Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 6-11